SPE Annual Technical Conference and Exhibition 1988
DOI: 10.2118/18221-ms
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Dispersion Viscosity of Oil/Water Mixture Flow in Horizontal Pipes

Abstract: SPE Members Abstract A pipe viscometer facility was constructed to investigate the flow of oil-water dispersions in horizontal pipes. Pressure drop, liquid mass flow rate, mixture temperature, Pressure drop, liquid mass flow rate, mixture temperature, input water fraction, and mixing intensity data were obtained for 490 oil-water tests. Mixture velocities ranged from 2.5 to 15.5 ft/sec, while input water fractions ranged from 0.0 to 0.35. Mixture temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…In fact, there was a marked difference between the profiles found from rheological analysis and for flowing pipe systems. [8,27,28] Arirachakaran [29] suggested a correlation between oil viscosity µ o and transition point f oi but in this work the relation was sometimes shown to fail. [19] Pan et al .…”
Section: Pressurementioning
confidence: 92%
“…In fact, there was a marked difference between the profiles found from rheological analysis and for flowing pipe systems. [8,27,28] Arirachakaran [29] suggested a correlation between oil viscosity µ o and transition point f oi but in this work the relation was sometimes shown to fail. [19] Pan et al .…”
Section: Pressurementioning
confidence: 92%
“…They found that the holdup was altered from the input volume fraction at a minimum flow rate and increased slip ratio. This trend, according to Charles et al (1961) and Martinez et al (1988), was due to the liquid that was in contact with the pipe. It was likely to accumulate in the tubes at a slower velocity.…”
Section: Researchers Likementioning
confidence: 95%
“…Soleimani et al (2000) found that the holdup was influenced by the input volume fraction at the minimum flow rate as well as the increase in slip ratio. This trend, according to Charles et al (1961) and Martinez et al (1988), was due to the contact between the liquid and the pipe, and the liquid was likely to be accumulating in the pipe at a slower velocity. When oil and water travelled concurrently in a pipe, oil was found to travel faster than water causing a slippage between the phases.…”
Section: Water Holdup Analysismentioning
confidence: 98%
“…The input parameters used in this work are oil slip velocity, water slip velocity, pipe diameter, pipe roughness and oil viscosity which are collected over 994 data point from experimental works of Trallero [20], Yipping et al [57], Nadler et al [58], Martinez et al [59], Angeli et al [6], Elseth [1], Lovick and Angeli [34], Chakrabarti [4], Rodriguez [3], Al-Wahaibi [60], Liu et al [61] and Al-Yaari et al [62] .…”
Section: Databankmentioning
confidence: 99%